Localização de Gravidade 4D em Branas SUSY - Silva, Rodrigo César Fonseca da (2013)
In the original RandallSundrum model, the 5D gravity is coupled to a negative cosmological constant and a 3brane sourced by a delta function. The solution in such setup is a symmetric solution given in terms of two copies of AdS5 spaces patched together along the 3brane. Although in this setup the fifth dimension is infinite the volume of the 5D bulk space is infinite because the geometry is warped. As a consequence this allows having graviton zero mode responsible for 4D gravity on the brane. This is not necessarily true for spaces whose volume diverges, because no zero mode emerges anymore. We investigate the localization of metastable 4D gravity around a assymetric flat brane and a bent dilatonic brane, embedded into a 5D space, that exists only up to distances suficiently small compared to a crossover scale. Far from such scale, 5D effects causing deviations in Newtonian potential. In this thesis, we present a study on this effect considering the location of massive gravity on a asymmetric flat brane and non-BPS and BPS bent dilatonic 3brane solutions of a supergravity 5D. The parameters control the thickness of the membrane also control the crossover scale of the first case. In the other hand, the cosmological constant on the bent brane controls the size of the crossover scale in second case. For suficiently small positive cosmological constant, that is in accord with the present observations, the crossover scale becomes very large. Thus, as emphasized in Gregory-Rubakov-Sibiryakov (GRS) and Dvali-Gabadadze-Porrati (DGP) scenarios, we shall focus on the main beautiful characteristic of the 4D metastable gravity, that is the fact that where as gravity becomes four-dimensional for distances very much smaller than the crossover scale, it emerges as a 5D gravity for distances very much larger than such scale. In doing so, we will find the Newtonian potential induced by the gravity massive modes of a Schroedinger-like equation for the gravity fluctuations around the brane solutions.